TEKNIK HUMOR ARTHUR ASA BERGER SEBAGAI MEDIA KRITIK SOSIAL PADA TAYANGAN LAPOR PAK! TRANS7 - Indriani, Rizki; Irfai Fathurohman; Ahmad Hariyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes humor techniques as an instrument of social criticism in the Lapor Pak! Trans7 through the lens of Arthur Asa Berger's theory. Using a qualitative descriptive approach, primary data was sourced from the speech in the episode "Troops Entrusted with 2 Trillion Corruption Proceeds" which was collected through the observation and recording technique, and analyzed using the Miles and Huberman model. The results showed the use of humor techniques that varied in the categories of language (irony, sarcasm, insults, puns), logic (comparison, absurdity, analogy, reversal, rigidity), and identity (identity, disclosure). The findings reflect five key themes of social criticism: bureaucratic hypocrisy, normalization of corruption, economic inequality, low administrative transparency, and closed official communication. It was concluded that the humor in the show is not just entertainment, but an effective satirical instrument that deconstructs sensitive sociopolitical issues in order to arouse the audience's critical awareness.